2016
DOI: 10.1016/j.neuroimage.2016.08.053
|View full text |Cite
|
Sign up to set email alerts
|

Functional activity and white matter microstructure reveal the independent effects of age of acquisition and proficiency on second-language learning

Abstract: Two key factors govern how bilingual speakers neurally maintain two languages: the speakers' second language age of acquisition (AoA) and their subsequent proficiency. However, the relative roles of these two factors have been difficult to disentangle given that the two can be closely correlated, and most prior studies have examined the two factors in isolation. Here, we combine functional magnetic resonance imaging with diffusion tensor imaging to identify specific brain areas that are independently modulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
58
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(68 citation statements)
references
References 63 publications
8
58
0
Order By: Relevance
“…The rapid development of the left inferior frontal region may be related to the inhibition or control of interference processes, as shown in our Stroop task. This finding is highly consistent with previous studies showing that the left inferior frontal cortex is important for bilinguals' executive functions (Jubin Abutalebi & Green, 2007;Hernandez & Li, 2007;Mårtensson et al, 2012;Stein et al, 2012), a key region also implicated in the AoA effect (Klein et al, 2014;Nichols & Joanisse, 2016). The middle fusiform region is an orthographically sensitive brain region modulated by literacy (Dehaene et al, 2010) and is also related to the competition processes of bilinguals' two languages (Tan et al, 2011), although we did not find that its microstructural properties (MTV and T1) were correlated with the Stroop effect.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The rapid development of the left inferior frontal region may be related to the inhibition or control of interference processes, as shown in our Stroop task. This finding is highly consistent with previous studies showing that the left inferior frontal cortex is important for bilinguals' executive functions (Jubin Abutalebi & Green, 2007;Hernandez & Li, 2007;Mårtensson et al, 2012;Stein et al, 2012), a key region also implicated in the AoA effect (Klein et al, 2014;Nichols & Joanisse, 2016). The middle fusiform region is an orthographically sensitive brain region modulated by literacy (Dehaene et al, 2010) and is also related to the competition processes of bilinguals' two languages (Tan et al, 2011), although we did not find that its microstructural properties (MTV and T1) were correlated with the Stroop effect.…”
Section: Discussionsupporting
confidence: 92%
“…So far there had been only a few studies that attempted to disentangle the effect of AoA from that of proficiency: Wartenburger et al showed that these two variables may differentially affect grammatical processing (AoA) versus semantic processing (proficiency) (Wartenburger et al, 2003). In a recent study, Nichols and Joanisse showed with their functional imaging data, consistent with their DTI data, that AoA modulated L2 processing in bilateral IFG inferior frontal gyrus and other regions, whereas proficiency modulated L2 processing in the right cingulate and left parahippocampus, suggesting that these two factors have independent contributions (Nichols & Joanisse, 2016). Our study further confirms that AoA and proficiency can play distinct roles contributing to the microstructure of the bilingual brain.…”
Section: Discussionmentioning
confidence: 79%
“…This pattern again underscores the point that the brain–behavior relationship between WM integrity and RT is complex, and that L2 experience modifies this relationship. Nichols and Joanisse revealed that, with earlier age of L2 acquisition, young adult bilinguals had higher FA values in the ILF, the anterior midbody of the corpus callosum, and the arcuate fasciculus. L2 proficiency was also associated with greater FA in the ILF, the right arcuate fasciculus, and the forceps minor of the corpus callosum.…”
Section: Greater Integrity Of White Matter Structures For Bilingualsmentioning
confidence: 99%
“…Whole‐brain analyses were conducted on 334 brain scans using general linear modeling to determine differences in brain structure relative to AoA. Because previous studies have found neuroanatomical effects associated with AoA by conducting analyses that treat AoA as categorical (i.e., Berken et al, ; Kaiser et al, ; Klein et al, ; Mohades et al, 2012) and continuous (i.e., Klein et al, ; Nichols & Joanisse, ; Wei et al, ), this study used both group comparisons (ANOVA) and regression analyses (in which AoA was treated as a continuous variable). Analyses of cortical thickness, volume, and density were conducted.…”
Section: Resultsmentioning
confidence: 99%
“…Whole-brain analyses were conducted on 334 brain scans using general linear modeling to determine differences in brain structure Berken et al, 2016b;Kaiser et al, 2015;Klein et al, 2014;Mohades et al, 2012) and continuous (i.e., Klein et al, 2014;Nichols & Joanisse, 2016;Wei et al, 2015), this study used both group comparisons (ANOVA) and regression analyses (in which…”
Section: Resultsmentioning
confidence: 99%